Estudos de compatibilidade fármaco-excipiente da azatioprina e da losartana potássica através de análise térmica - Carolina Rossi Gouvea Silva (2017)
Aiming to evaluate possible interactions between the drugs azathioprine (AZA), potassium losartan (LOP) and a series of excipients used in commercial formulas, the binary mixtures drug-excipient were evaluated by Differential Scanning Calorimetry (DSC), X-Ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR). From DSC analysis, interactions were observed in elevated temperatures for the binary mixtures formed by AZA-colloidal silicon dioxide, AZA-magnesium stearate, LOP-monohydrated lactose, LOP-magnesium stearate, LOP-monocrystalline cellulose and LOP-sodic starch glycolate. The compatibility study using DRX and FTIR did not evidenced clues of interaction. After eight months of direct contact between drugs and excipients, the binary mixtures were submitted again to DSC and DRX analysis. After an extended period of exposition, the thermal behaviour of the binary mixtures was maintained, but interactions were verified through XRD experiments between AZA-colloidal silicon dioxide, AZA-mannitol, AZA-magnesium stearate, LOP and all the studied excipients. The concentration of excipients in the final formula must be taken into account, once the 1:1 proportion of the drug-excipient binary mixtures used in this study has a goal of intensifying possible interactions.